Exercício das funções parentais e funcionamento de linguagem em três casos de risco psíquico - Flores, Mariana Rodrigues (2012)
This study was guided by psychoanalytic and enunciative theoretical approaches. The purpose of this study is to investigate the relationships between the presence of risks to the child development and exercise of maternal and paternal functions, and their effects on the language acquisition process by babies as occupying a place of enunciation. The method consisted of a qualitative design with a sample of three children who present developmental risk, which is, mainly, related to paternal function. The childre were evaluated from 0 to 18 months after the, and a semi structured interview with parents, which were verified according to content analysis. Besides, there were filmed samples of each child with their fathers and mothers, who were analyzed through the Silva’s (2007) enunciative language acquisition aproach and language evaluation theoretical principles (SURREAUX, 2006; CARDOSO, 2010), that have Benveniste as theoretical reference. The results of the study showed that the risks were found in parent’s speeches, what evidenced weakness by fathers to establish their function in all cases; moreover, it was observed that the children were construting language semiotic level , but the dialogue were restrict to a single interlocutor, the mother, what is related, in the analyzed cases, to difficulty of mother-baby separation and the no establishment of paternal function. This study demonstrates the relevance of further studies to increase the precocious detection in cases of psychical risk before the pathologies are installed in children. The language data demonstrated that the enunciative aproach brings important aspects for research language analisys and that it qualifies early detection and intervention.